Modern Management of Dyslipidemia: A Comprehensive Review Study (The Review of Diabetic Studies, 2025)
Dyslipidemia is the metabolic derangement of the lipids in the body, which is often only diagnosed through a blood lipid profile. It is a common pathology affecting the majority of the adult population, with a high disease burden on the healthcare system due to its complications. A better understanding of the latest treatment modalities can aid in providing better care for the patients.Aim of the study: To establish a better understanding of the symptoms, diagnostic methodology, and management of dyslipidemia.Materials and methods: This review is a comprehensive search of PUBMED from the year 2021 to 2024.Conclusion: Dyslipidemia is a silent pathology that requires regular screening and prompt treatment to prevent long-term complications and possible morbidity. Better knowledge about the latest guidelines and treatment modalities can aid physicians in providing optimal care for their patients.